hERG activators exhibit antitumor effects in breast cancer through calcineurin and β-catenin-mediated signaling pathways - Yu, Yan; Zhu, Chengchun; Wang, Xiao; Shi, Ying; Gao, Yiping; Yu, Zhiyi (Frontiers in Pharmacology, 2025)
BackgroundBreast cancer remains a leading cause of mortality among women worldwide, with existing therapeutic options often accompanied by significant side effects and a persistent risk of disease recurrence. This highlights the need for novel drug candidates with new mechanisms of action by targeting alternative signaling pathways. While hERG channel is notoriously regarded as an off-target due to drug-induced cardiotoxicity, its therapeutic potential as a drug target remains largely unexplored.MethodsThis study investigated the role of hERG in breast cancer progression and its impact on patient survival. The anti-proliferative, anti-migratory, anti-invasive and pro-apoptotic effects of hERG activators were evaluated using the Cell Counting Kit-8, wound healing assay, transwell assay and cell apoptosis assay, respectively. Western blotting, Ca2+ imaging and immunofluorescence assays were employed to study their antitumor mechanisms of actions.ResultsWe identified two novel hERG activators, SDUY429 and SDUY436, which effectively inhibited the proliferation and migration of MDA-MB-231 and MCF-7 cells. In addition, SDUY436 demonstrated significant anti-invasive and pro-apoptotic effects in MDA-MB-231 cells. Mechanistically, the anti-proliferative activity of hERG activators were mediated through calcineurin activation via enhanced calcium ion influx, which facilitated the nuclear translocation of nuclear factor of activated T cells (NFAT) and upregulated p21Waf/Cip expression. Furthermore, both SDUY429 and SDUY436 remarkably suppressed the migration and invasion of MDA-MB-231 cells by downregulating the protein kinase B (AKT)/glycogen synthase kinase-3 beta (GSK3β)/β-catenin signaling pathway. The observed reduction in phospho-AKT-Ser473 (pAKTS473) expression resulted in the decreased levels of phospho-GSK3β-Ser9 (pGSK3βS9), thereby limiting the nuclear localization of β-catenin, which led to the inhibition of cell migration and invasion. Notably, combining SDUY429 or SDUY436 with the AKT inhibitor MK-2206 produced synergistic anti-proliferative effects.ConclusionThese findings suggest that hERG activators hold promise as new potential therapeutic agents for the treatment of breast cancer, paving the way for future investigations into their clinical applications.